2010
DOI: 10.1073/pnas.1006689107
|View full text |Cite
|
Sign up to set email alerts
|

Vectors and parameters that enhance the efficacy of RNAi-mediated gene disruption in transgenic Drosophila

Abstract: Whole-genome transgenic RNAi libraries permit systematic genetic screens in individual tissues of Drosophila . However, there is a high incidence of nonspecific phenotypes because of off-target effects. To minimize such effects, it is essential to obtain a deeper understanding of the specificity of action of RNAi. Here, in vivo assays are used to determine the minimum, contiguous nucleotide pairing required between an siRNA and a target mRNA to generate a phenotype. We observe that as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…Since microRNAs (miRNA)-based gene silencing has minimal cross-interference and more efficient knockdown effect (Chen et al, 2007; Haley et al, 2010; Ni et al, 2011), we employed this system. In the compound eyes, mi-grim and mi-rpr showed a complete rescue of GMR-grim and GMR - rpr -induced cell death, respectively, and these lines did not display cross-interference (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since microRNAs (miRNA)-based gene silencing has minimal cross-interference and more efficient knockdown effect (Chen et al, 2007; Haley et al, 2010; Ni et al, 2011), we employed this system. In the compound eyes, mi-grim and mi-rpr showed a complete rescue of GMR-grim and GMR - rpr -induced cell death, respectively, and these lines did not display cross-interference (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our search was focused on nucleotides 2–18 because previous studies suggested that pairing of the 5′ terminal nucleotide of the small RNA with its target is not required for efficient silencing. Furthermore, several mismatches between the 3′ end of the small RNA and the target site can be tolerated for target regulation 44,45 .…”
Section: Methodsmentioning
confidence: 99%
“…Using the Designer of Small Interfering RNA algorithm, we chose two sets of shRNA sequences for the TOP2 gene, with one targeting the protein-coding region and the other targeting the 3Ј UTR (21). In case of insufficient knockdown efficiency by a single shRNA, we employed two approaches to combine the effect of two shRNAs either from two separate plasmids or with tandem-linked shRNAs on a single plasmid (20). As described by Haley et al (20), the shRNA sequence is embedded in an ftz intron upstream of a GFP reporter gene, which allowed us to track the induction of the shRNA at the single cell level by fluorescence-activated cell sorting.…”
Section: Phosphorylation Of Both Ser-1428 and Ser-1443 Is Requiredmentioning
confidence: 99%
“…We adapted an intron-mediated shmiR expression system to generate an inducible plasmid-based shRNA system to simultaneously silence endogenous Top2 and express the WT or mutant Top2 (Fig. 6A) (20). Using the Designer of Small Interfering RNA algorithm, we chose two sets of shRNA sequences for the TOP2 gene, with one targeting the protein-coding region and the other targeting the 3Ј UTR (21).…”
Section: Phosphorylation Of Both Ser-1428 and Ser-1443 Is Requiredmentioning
confidence: 99%
See 1 more Smart Citation